Personality Traits in Frederict Backman’s Novel A Man Called Ove - Natalia, C W (KnE Social Sciences, 2018)
This research talks about the Protagonist’s Personality Traits in Frederick Backman’s Novel A Man Called Ove. The focus of the analysis will be on the Extrovert and Introvert personalities of the first character of the novel by the name of Ove. The purpose of this research is to reveal as well as to analyze the protagonist’s personality that is clearly seen in this novel. The extrovert and introvert personalities were analyzed by using the Psychological theory as well as approach proposed by Carl Gustav Jung (1921). The research method used in this research was qualitative research proposed by John Creswell (2008). The result of this research shows that the protagonist possesses extrovert and introvert personalities which are reflected in the novel. It is clearly revealed that there are 51 sentences in the novel that show protagonist’s personalities of extrovert and 62 sentences that show the personalities of introvert. Keywords: personality traits, extrovert, introvert.